2012
DOI: 10.1017/s1751731111002175
|View full text |Cite
|
Sign up to set email alerts
|

The roles of different porcine cytochrome P450 enzymes and cytochrome b5A in skatole metabolism

Abstract: Boar taint is the unfavourable odour and taste from pork fat, which results in part from the accumulation of skatole (3-methylindole, 3MI). The key enzymes in skatole metabolism are thought to be cytochrome P450 2E1 (CYP2E1) and cytochrome 2A (CYP2A); however, the cytochrome P450 (CYP450) isoform responsible for the production of the metabolite 6-hydroxy-3-methylindole (6-OH-3MI, 6-hydroxyskatole), which is thought to be involved in the clearance of skatole, has not been established conclusively. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 26 publications
(36 reference statements)
1
44
2
Order By: Relevance
“…This, however, needs further investigation. CYP2A19 was not involved in HMOI formation (as supported by Wiercinska et al, 2012). CYP2E1 was involved in the formation of 3MOI in both male and female pigs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…This, however, needs further investigation. CYP2A19 was not involved in HMOI formation (as supported by Wiercinska et al, 2012). CYP2E1 was involved in the formation of 3MOI in both male and female pigs.…”
Section: Discussionmentioning
confidence: 81%
“…CYP2C (sulphaphenazole) and CYP1A2 (furafylline) were not involved in the formation of HMOI in either male or female pigs. On the contrary, involvement of CYP2C and CYP1A2 was demonstrated by previous in vitro studies (Wiercinska et al, 2012). The disagreement between these studies might be because of the different in vitro systems used.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This finding was later confirmed by Borrisser Pairó et al (2015). In contrast, Wiercinska et al (2011) demonstrated formation of I3C by porcine CYP2E1 expressed in the human embryonic kidney HEK293-FT cell line. MOI and HMOI were repeatedly shown to be produced by several CYP450 isoforms, including CYP2E1 and CYP2A19 (Zamaratskaia and Squires, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…The importance of cytochrome P450 (CYP450; especially CYP1A, CYP2A and CYP2E1) in skatole metabolism is well established (Babol et al, 1998;Diaz and Squires, 2000;Zamaratskaia et al, 2005;Matal et al, 2009;Wiercinska et al, 2011). Currently, seven skatole metabolites are known, indole-3-carbinol (I3C), 2-aminoacetophenone (AAP), 3-hydroxy-3-methyloxindole (HMOI), 3-methyloxyindole (MOI), 3-hydroxy-3-methylindolenine, 5-hydroxy-3-methylindole and 6-hydroxy-3-methylindole (6-OH-3MI) (Baek et al, 1997;Diaz et al, 1999;Borrisser Pairó et al, 2015).…”
Section: Introductionmentioning
confidence: 99%